Insights for increased risk of failed fibrinolytic therapy and stent thrombosis associated with COVID‐19 in ST‐segment elevation myocardial infarction patients. Issue 2 (30th April 2020) - Lacour, Thibaud; Semaan, Carl; Genet, Thibaud; Ivanes, Fabrice
Abstract: Important health resources are dedicated worldwide to the management of COVID‐19. This new disease, due to its large diffusion, may significantly hamper the prognosis of other pathologies, such as ST‐segment elevation myocardial infarction (STEMI) because of (a) a possible direct negative impact and (b) shortage of first response medical resources and increased delays to reperfusion. We report the case of a 68‐year‐old man admitted for anterior STEMI and asymptomatic COVID‐19. Due to extended transportation delays to a cathlab, he received intravenous fibrinolytic therapy, which failed. Reperfusion was achieved with rescue coronary angioplasty, but the patient experienced two episodes of acute stent thrombosis at 2‐ and 36‐hr following admission and despite optimal medical therapy. He finally died because of cardiogenic shock. This raises concerns about a possible increase in platelet aggregability associated with COVID‐19 leading to an increased risk of stent thrombosis, particularly in the context of STEMI. This pleads for the promotion of primary coronary angioplasty as the first‐choice revascularization technique in this population and the use of new generation P2Y12 inhibitors. In addition, the use of GPIIb/IIIa inhibitors may be considered in every STEMI patient with COVID‐19 to prevent the risk of acute stent thrombosis.